Deciphering host factors for mycobacteria internalization during phagocytosis - Timóteo, Pedro Manuel Dias, 1990- (2013)
Tese de mestrado. Biologia (Microbiologia Aplicada). Universidade de Lisboa, Faculdade de Ciências, 2013